Exfoliative Cytology for Age Evaluation: A Comparative Study in Different Age Groups - Manvikar, Dr. Vardendra; M R, Dr. Pradeep; Latha H, Dr Aparna; N G, Dr. Shreekanth; Velpula, Dr. Vijaya Kumar; Reddy, Dr. K. M. Parveen (International Journal of Innovative Research in Medical Science, 2025)
Introduction: In the context of a criminal investigation or a mass tragedy, determining the age of missing human remains is crucial because details like gender, birthdate and year of death can help investigators narrow down a vast pool of potential matches and identify the right person. Oral exfoliative cytology is a simple, relatively easy procedure that requires little discomfort from the patient to be repeated. Objective: The purpose of the study was to use image analysis morphometric software to compare the average cell size in buccal smears in order to estimate an individual's age. Materials and Methods: Buccal smears were collected from 100 apparently healthy individuals. The smears were stained according to the standard Papanicolaou laboratory protocol after being fixed in 95% alcohol. The image analysis program version 4.3 from Dewinter was used to calculate the average cell size. Results: The average cell size of each individual significantly decreased as age increased, according to the results. The average cell size decreased with age, according to cytomorphometry. A statistically significant reduction in the average cell size was revealed by analysis, using one-way ANOVA and Bonferroni methods (P < 0.005). Conclusion: Buccal smears show age-related changes that can be utilized as an age estimation technique. Compared to other screening modalities, which are typically either invasive or costly, cytomorphometric examination of exfoliated cells of the buccal mucosa offers as a potential alternative non-invasive approach in evaluation and correlation of an individual's age.